Strategy Configurations Directly Linked to Higher Hepatitis C Virus Treatment Starts: An Applied Use of Configurational Comparative Methods. Issue 5 (May 2020) - Yakovchenko, Vera; Miech, Edward J.; Chinman, Matthew J.; Chartier, Maggie; Gonzalez, Rachel; Kirchner, JoAnn E.; Morgan, Timothy R.; Park, Angela; Powell, Byron J.; Proctor, Enola K.; Ross, David; Waltz, Thomas J.; et al.
Abstract : Background: The Department of Veterans Affairs (VA) cares for more patients with hepatitis C virus (HCV) than any other US health care system. We tracked the implementation strategies that VA sites used to implement highly effective new treatments for HCV with the aim of uncovering how combinations of implementation strategies influenced the uptake of the HCV treatment innovation. We applied Configurational Comparative Methods (CCMs) to uncover causal dependencies and identify difference-making strategy configurations, and to distinguish higher from lower HCV treating sites. Methods: We surveyed providers to assess VA sites' use of 73 implementation strategies to promote HCV treatment in the fiscal year 2015. CCMs were used to identify strategy configurations that uniquely distinguished higher HCV from lower HCV treating sites. Results: From the 73 possible implementation strategies, CCMs identified 5 distinct strategy configurations, or "solution paths." These were comprised of 10 individual strategies that collectively explained 80% of the sites with higher HCV treatment starts with 100% consistency. Using any one of the following 5 solution paths was sufficient to produce higher treatment starts: (1) technical assistance; (2) engaging in a learning collaborative AND designating leaders; (3) site visits AND outreach to patients to promote uptake and adherence; (4) developing resource sharing agreements AND an implementation blueprint; OR (5) creating new clinical teams AND sharing quality improvement knowledge with other sites AND engaging patients. There was equifinality in that the presence of any one of the 5 solution paths was sufficient for higher treatment starts. Conclusions: Five strategy configurations distinguished higher HCV from lower HCV treating sites with 100% consistency. CCMs represent a methodological advancement that can help inform high-yield implementation strategy selection and increase the efficiency and effectiveness of future implementation efforts.